2021
DOI: 10.3390/ma14030663
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Process Conditions on Surge Current Capability of 1.2 kV SiC JBS and MPS Diodes

Abstract: This paper demonstrated the impact of process conditions on the surge current capability of 1.2 kV SiC junction barrier Schottky diode (JBS) and merged PiN Schottky diode (MPS). The influence of ohmic contact and defect density produced by implantation was studied in the simulation. The device fabricated with high temperature implantation had less defect density in the implant region compared with room temperature implantation, which contributed to higher hole injection in surge current mode and 20% surge capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…In figures 11(a) and (c), an interesting phenomenon can be found that the peak value of both voltage and current will shift to the left. A similar phenomenon is also observed in 4 H-SiC MPS diode [35]. From the perspective of the resonant circuit, CSBR can be considered as a variable resistance.…”
Section: Surge Current Capabilitysupporting
confidence: 68%
“…In figures 11(a) and (c), an interesting phenomenon can be found that the peak value of both voltage and current will shift to the left. A similar phenomenon is also observed in 4 H-SiC MPS diode [35]. From the perspective of the resonant circuit, CSBR can be considered as a variable resistance.…”
Section: Surge Current Capabilitysupporting
confidence: 68%
“…This chip-temperature model, given by Eqs. (10) and (11), is verified by experimental data in the following section.…”
Section: Chip Temperature Modelsupporting
confidence: 57%
“…However, in addition to the thermal resistance, another fundamental parameter that impacts the SiC chip temperature is the thermal capacitance. As a result of wafer thinning practices, the thermal capacitance of the SiC chip is reduced, which has an opposing effect to the thermal resistance in terms of the SiC chip temperature during surge-current events.The capability of Schottky diodes to withstand surge currents has been extensively reported in published literature, as it is regarded as one of the most significant reliability factors of power devices [10][11][12][13][14][15][16][17][18][19] . However, the association between wafer thinning and the surge-current capability of a Schottky diode is a novel field of research, with studies predominately reporting on the beneficial influence of wafer thinning as a way of enhancing the surge-current capability.…”
mentioning
confidence: 99%
See 1 more Smart Citation